Undifferentiated embryonal sarcoma of the liver occurring in an adolescent: a case report with genomic analysis - Tomonari Shimagaki; Keishi Sugimachi; Yohei Mano; Emi Onishi; Yuki Tanaka; Rie Sugimoto; Kenichi Taguchi; Masaru Morita; Yasushi Toh (Surgical Case Reports)
Abstract Background Undifferentiated embryonal sarcoma of the liver (UESL) is a rare malignant mesenchymal tumor that usually occurs in children and is rarely diagnosed in adults. Case presentation The case was a female in her late 20s who presented with a huge liver mass found upon the examination of fever. Imaging analysis showed a well-defined mass measuring 9 cm in the largest dimension in the right posterior segment of the liver. The patient underwent right hemi-hepatectomy. Histopathological studies revealed that the circumscribed tumor was composed of a proliferation of atypical epithelioid to spindle-shaped cells with pleomorphic nuclei arranged in haphazard pattern. Histopathological features observed in immunohistochemical analyses confirmed a final diagnosis of UESL. Genome analysis using FoundationOne CDx revealed 11 somatic mutations including TP53 (R196*) and STK11 (F354L). Adjuvant chemotherapy with ifosfamide and etoposide was performed, and the case has been followed up without recurrence for 1 year after hepatectomy. Conclusions A UESL should be considered in the differential diagnosis of large and well-defined solid liver lesions. Although the prognosis of UESL is extremely unfavorable, aggressive surgical resection with adjuvant chemotherapy and genomic analysis may be helpful for ensuring long-term survival.